The Formation and Development of Uzbek Folk Music - Mamarasulzoda A Zulhumor (International Journal on Integrated Education, 2021)
The rich musical heritage accumulated by our ancestors for many years, the life experiences of teachers, their unique traditions, later polished in the musical views of scholars who grew up on this land, acquired a scientific character and sealed in unique manuscripts and turned into a spiritual heritage. The study of this heritage, the enrichment of new qualities and their introduction into consumption is one of the most pressing issues in the current development of our society, the process of spiritual growth, the restoration of traditions and values.